Annual Report on Exchange Arrangements and Exchange Restrictions 2000. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2000)
The exchange and trade systems of IMF member countries are presented in this comprehensive volume in a tabular format. There is expanded coverage of the regulatory framework for capital movements. The information generally relates to the end of 1999 but also covers significant developments in early 2000. Published in Septermber.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet